2012
DOI: 10.1038/modpathol.2011.142
|View full text |Cite
|
Sign up to set email alerts
|

Association of microRNA-21 expression with its targets, PDCD4 and TIMP3, in pancreatic ductal adenocarcinoma

Abstract: Since the discovery of small non-coding RNAs, the analyses of microRNA (miRNA) expression patterns in human cancer have provided new insights into cancer biology. miRNA-21 has been suggested to be one of the miRNAs that have an important role in the development or biological behavior of a variety of malignancies, including pancreatic cancer. This study was conducted to evaluate the relationship between the expression of miRNA-21 and that of its molecular targets, programmed cell death 4 (PDCD4) and tissue inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 31 publications
(32 reference statements)
5
91
0
3
Order By: Relevance
“…MiR-21 was up-regulated in pancreatic adenocarcinomas in this and other studies and has been related to short survival. 20,22,38,39 Increased miR-21 expression increases the proliferative and invasive potential in several types of cancer, it has anti-apoptotic and pro-angiogenesis properties and its expression may represent an adaptation to a hypoxic environment that favors cancer cell survival. 40 In accordance with others, we found that miR-148a, miR-216b and miR-217b were some of the miRNAs with the most significantly decreased expression in pancreatic adenocarcinomas compared with chronic pancreatitis and normal pancreas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-21 was up-regulated in pancreatic adenocarcinomas in this and other studies and has been related to short survival. 20,22,38,39 Increased miR-21 expression increases the proliferative and invasive potential in several types of cancer, it has anti-apoptotic and pro-angiogenesis properties and its expression may represent an adaptation to a hypoxic environment that favors cancer cell survival. 40 In accordance with others, we found that miR-148a, miR-216b and miR-217b were some of the miRNAs with the most significantly decreased expression in pancreatic adenocarcinomas compared with chronic pancreatitis and normal pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…40 In accordance with others, we found that miR-148a, miR-216b and miR-217b were some of the miRNAs with the most significantly decreased expression in pancreatic adenocarcinomas compared with chronic pancreatitis and normal pancreas. 21,39 Over-expression of miR-217 in pancreatic adenocarcinoma cells inhibits tumor cell growth in vivo and in vitro. 41 Expression of miR-217 is negatively related to KRAS expression.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported that miR-21 plays an important role not only in tumor growth but also in the invasion and metastasis by targeting multiple tumor suppressor genes including PTEN, PDCD4, BCL-2, TPM1, and RECK (Zhu et al, 2007;Asangani et al, 2008;Gabriely et al, 2008;Zhang et al, 2008b;Zhu et al, 2008;Nagao et al, 2012;Zhang et al, 2012). PTEN (phosphatase and tensin homolog deleted on chromosome 10) (Li et al, 1997) is one of the most frequently inactivated tumor suppressors indifferent tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of miR-21 has been shown to be involved in the progression of several types of cancers (Kwak et al, 2011;Yang et al, 2011), including PDAC (Bloomston et al, 2007;Szafranska et al, 2007;Nagao et al, 2012), and the up-regulation of miR-21 expression has been shown to correlate with a lower cancer survival rate (Dillhoff et al, 2008;Jamieson et al, 2012). Recent studies also demonstrated that miR-21 modulates the chemosensitivity of cancer cells primarily by targeting PTEN or PDCD4 (Moriyama et al, 2009;Ali et al, 2010;Giovannetti et al, 2010;Tomimaru et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Cząsteczka miRNA-21 funkcjonuje jako onkogen w przebiegu gruczolakoraka trzustki i w znacznej liczbie przypadków chorych obserwowana jest jej nadekspresja, co jest związane z wystąpieniem przerzutów do węzłów chłonnych oraz gorszym rokowaniem [16].…”
Section: Nowotwory Trzustkiunclassified